Resistance of rice cultivars to Rhizoctonia solani and Rhizoctonia oryzae - Prabhu, Anne Sitarama; Filippi, Marta Cristina; Silva, Gisele Barata da; Santos, Gil Rodrigo de (Pesquisa Agropecuaria Brasileira, 2002)
Isolates of Rhizoctonia solani and Rhizoctonia oryzae, the causal agents of sheath blight and sheath rot diseases, respectively, were collected from irrigated rice fields in the State of Tocantins, Brazil. The main objective of the investigation was to assess the resistance of 12 genotypes to these diseases, under artificial inoculation tests in greenhouse condition. There was no correlation between the resistance of cultivars to R. oryzae and R. solani for lesion extension on sheath infection obtained by the toothpick method. The relationship between lesion size on sheath and leaf was linear and significantly negative (r = - 0.66, P£0.05), thereby indicating that there is no relationship between resistance of sheath and leaf to infection by R. solani in rice cultivars. Among the early maturing genotypes Labelle was highly susceptible in all methods of inoculation. The area under disease progress curve based on lesion height on the culm and the inoculation method with rice husk and grain were found more adequate for determining the differences in the degree of resistance among cultivars. Leaves exhibited resistance to infection by R. oryzae in inoculation tests with mycelial discs.